Male-Female Wage Differentials and Policy Responses - Gunderson, Morley (Journal of Economic Literature, 1989)
Without implicating them for any of the contents of the paper, I am grateful to the following for helpful discussions or comments: Andrea Beller (University of Illinois), David Bloom (Harvard and Columnbia), Glen Cain (University of Wisconsin), Ron Ehrenberg (Cornell), Victor Fuchs (Stanford), Bob Gregory (Australian National University), Jonathan Leonard (University of California, Berkeley), Roberta Robb (Brock University), and Paul Weiler (Harvard). Financial support of the Humanities and Social Sciences Committee of the Research Board of the Universitu of Toronto is eratefullu acknowlede,ed.